Sosialisasi Penerapan Metode SWOT Pada Perancangan Strategi Daya Saing Terminal Kendaraan Pelabuhan Patimban - Sri Rahardjo Suwito; Tedy Herdian; Anton Ferdiansyah; Iqbal Firmansyah; Karen Nevia Abigail Ponto (Institut Transportasi dan Logistik Trisakti, 2023)
Motorized vehicles are one of Indonesia's leading products, which every year experience an increase in distribution flows between regions. Sea transportation has an important role in the distribution of motorized vehicles. Therefore, adequate port infrastructure is needed. Patimban Port is one of the National Strategy Projects during the reign of President Joko Widodo based on the Decree of the Minister of Transportation No. 87 of 2017 concerning the Port Master Plan which aims to reduce logistics costs and is expected to increase the competitiveness of ports in Indonesia. Currently Patimban Port does not have a good development strategy. This is one of the problems in efforts to improve port competitiveness. The method of presentation is carried out using the zoom provided by the Lecturers of the Trisakti Institute of Transportation and Logistics (ITL) which aims to provide an explanation of port development, port competitiveness and the SWOT method. The results of this community service prove that the presentation of PkM material is very useful and overall implementation has been very good and very appropiate to the industry situation.